Flexible magnetic filaments under the influence of external magnetic fields in the limit of infinite dilution. Issue 18 (20th April 2016) - Cerdà, Joan J.; Sánchez, Pedro A.; Lüsebrink, Daniel; Kantorovich, Sofia; Sintes, Tomàs
Abstract : The presence of an external magnetic field enables the existence of bistable and multi-stable regions in the phase diagram of magnetic filaments. Abstract : In the present work we use Langevin dynamics computer simulations to understand how the presence of a constant external magnetic field modifies the conformational phase diagram of magnetic filaments in the limit of infinite dilution. We have considered the filaments immersed in either a good (non-sticky filaments) or a poor (Stockmayer polymers) solvent. It has been found that in the presence of an applied field, filaments turn out to be much more susceptible to parameters such as temperature and solvent conditions. Filaments owe this increased susceptibility to the fact that the external magnetic field tends to level the free energy landscape as compared to the zero-field case. The field induces equalization in the free energy of competing conformational states that were separated by large energy differences in the zero-field limit. In this new scenario multistability arises, and manifests itself in the existence of broad regions in the phase diagram where two or more equilibrium configurations coexist. The existence of multistability greatly enhances the possibility of tuning the properties of the filament.